System Thinking Approach to Analyze Violations in the Distribution of Prescription Medicines in West Sumatra Province - Putra Gusrianto; Yos Sunitiyoso (Journal of International Conference Proceedings (JICP), 2021)
Indonesia has a high rate of illegal prescription medicine sales through unauthorized distribution facilities, and these violations have increased in the midst of the COVID-19 pandemic. Despite the fact that law enforcement has been conducted, it has continued to grow. Between 2018 and 2020, criminal cases related to this issue handled by the Indonesian Food and Drug Authority (BPOM) increased by 5.54 percent, and in the province of West Sumatra, which was the main focus of this study, cases of prescription medicine violations reached 68.35 percent in 2020. However, preventing and eradicating these cases has become increasingly difficult due to the interconnectedness of factors and actors. To address the issue, the system thinking approach was chosen as the best method for modeling the dynamic behavior of this complex system over time. To facilitate applicable solutions to resolve these violations that occur in West Sumatra Province, a tool known as a rich picture diagram (RPD) is proposed as a precursor to the development of a causal loop diagram (CLD). The study's system thinking approach enables the Indonesian Food and Drug Authority's business processes to fully comprehend the dynamics and develop robust systemic interventions during the supervision and investigation of such violations.